The THE INFLUENCE OF BOPO, ROA, LDR, AND FIXED ASSET INTENSITY ON TAX AGGRESSIVENESS IN BANKING COMPANIES - Natasya Hariyanto; Sartika Wulandari; Rachmawati Meita Oktaviani (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This research aims to examine the influence of BOPO, return on assets, loan to deposit ratio and fixed asset intensity on tax aggressiveness. The population in this research are banking sub-sector companies listed on the Indonesia Stock Exchange in 2019-2023. The number of samples in this research was 30 companies. The sampling technique uses a purposive sampling method. The research method used is quantitative with data sources in the form of secondary data. The data analysis method uses multiple linear regression analysis with SPSS version 22. The results of this research provide empirical evidence that partially the return on assets and loan to deposit ratio variables have an effect on tax aggressiveness. Meanwhile, the BOPO variables and fixed asset intensity have no effect on tax aggressiveness.